Early Intracranial Hemorrhage Predicts Poor Clinical Outcome in Community-Acquired Bacterial Meningitis - Weller, Johannes; Enkirch, Jonas Simon; Lehmann, Felix; Radbruch, Alexander; Klockgether, Thomas; Zimmermann, Julian (Frontiers in Neurology, 2022)
Background: Community-acquired bacterial meningitis in adults is associated with significant morbidity and mortality, therefore early prognostication is important to identify severe cases and possibly allocate more intensive treatment. We hypothesized that early intracranial hemorrhage portends a poor prognosis. Objective of this study was to evaluate the prognostic impact of early intracranial hemorrhage regardless of size and location on clinical outcome. Methods: Retrospective analysis of patients with community-acquired bacterial meningitis treated at a tertiary academic center between 2009 and 2019 with regard to patient characteristics, cerebral imaging findings and clinical outcome. Uni- and multivariable logistic regression analyses were performed to identify independent predictors of poor clinical outcome defined as a modified Rankin scale score of 5 or 6 upon discharge. Results: 102 patients were included, of which 22.5% had poor clinical outcome. Intracranial micro- or macrohemorrhages were present in 7.8% of cases and associated with poor clinical outcome (odds ratio [OR] 55.75, 95% CI 3.08-1008.48, p=0.006) in multivariate analysis, further predictors included ischemic stroke (OR 15.06, 95% CI 1.32-172, p=0.029), age (OR 2.56, 95% CI 1.4-4.67, p=0.002) and reduced consciousness (OR 4.21, 95% CI 1.07-16.64, p=0.04). Conclusion: Early cerebral hemorrhage (ECHO) is a potential prognostic marker for clinicians confronted with decision-making in critically ill patients with community-acquired bacterial meningitis.